Key research concepts in politics & international relations - Harisson, Lisa (SAGE key concepts, 2013)
This book is designed for students of Politics and International Relations at both undergraduate and postgraduate level. It provides explanations of fifty core concepts in political research methods and, uniquely, explains how these methods can be used in International Relations. Where relevant, alternative research concepts and strategies are suggested. Each 'concept' will incorporate a simple definition, a focused explanation, an examination of key debates and areas of research, along with cross-references to other related concepts. This format allows students and researchers alike to utilise the text either as a companion to specific modules, or on a 'dip into' basis.